Factors Associated to Positive Aspects in Caregiving for People Living with Dementia in Family Caregivers - Dian Pratiwi; Retno Indarwati; Rr. Dian Tristiana (Media Keperawatan Indonesia, 2021)
Caring for People with Dementia (PwD) has various negative effects that are detrimental to caregivers. The existence of Positive Aspects of Caregiving (PAC) makes the experience of caring for PwD more positive, valuable and protects caregivers from various negative impacts while caring for PwD. This study aims to explain the factors associated with PAC. These literature reviews were accessed from six databases (Scopus, CINAHL, Science Direct, ProQuest, PubMed, and SAGE Journal), with the keywords factor, positive aspects of caregiving, Dementia/ Alzheimer’s, during January 2021, limited to 2016-2020, and in English. A total of 318 journals were selected using PRISMA, then leaving 16 journals to be analyzed using The Joanna Briggs Institution Checklist. Sixteen journals were analyzed and divided into two themes, factors that affect PAC (n = 9) and factors affected by PAC (n = 7). Factors that affect PAC are caregiver characteristics, care-recipient characteristics, and social support. Factors affected by PAC are caregiving outcomes. Factors that increase PAC are lower education level, good social support, severe BPSD, shorter duration of care, and relationship with care-recipient (except spouse), and gender (male). The mediating factors that increase PAC are unmet needs and reciprocal filial piety. Factors that lower PAC are higher education level, the use of avoidance coping, and older age. We found inconsistencies in caregiver marital status and relationship with care-recipient because the finding still uncertain.